Megaesophagus secondary to myasthenia gravis in a female German shepherd dog - Andrade, Silvia Franco; Nogueira, Rosa Maria Barilli; Melchert, Alessandra; Silva, Maria Patrícia Chegança da; Motta, Yudney Pereira da; Brinholi, Rejane Batista; Tostes, Raimundo Alberto; Sanches, Osimar (Semina: Ciências Agrárias, 2007)
<span style="font-size: 10pt; color: #000000; font-family: TimesNewRoman; mso-bidi-font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;"> Megaesophagus is a common cause of regurgitation being one of the possible etiologies the myasthenia gravis characterized by a neuromuscular disorder that result in weakness of the skeletal muscles, of the esophagus, of the larynx and of the pharynx. The present report describes a case of a female German shepherd dog, with report of muscles weakness and frequent vomits, which was diagnosed as a megaesophagus secondary to myasthenia gravis. The radiograph of the animal presented an accentuated cervical and thoracic megaesophagus. After the institution of the recommended therapeutic protocol the animal presented visible improvement when walking, however the regurgitations worsened and it began to present cough. New radiograph was accomplished with presence, besides megaesophagus, of aspiration pneumonia. The owner opted for the euthanasia of the animal and the necropsy revealed severe pneumonia and an accentuated dilation of the posterior portion of the esophagus, collaborating with subsidies for an unfavorable prognostic of the case.